CCL20 is a novel ligand for the scavenging atypical chemokine receptor 4. Issue 6 (12th June 2020) - Matti, Christoph; D'Uonnolo, Giulia; Artinger, Marc; Melgrati, Serena; Salnikov, Angela; Thelen, Sylvia; Purvanov, Vladimir; Strobel, Tobias D.; Spannagel, Lisa; Thelen, Marcus; Legler, Daniel F.
Abstract: The chemokine CCL20 is broadly produced by endothelial cells in the liver, the lung, in lymph nodes and mucosal lymphoid tissues, and recruits CCR6 expressing leukocytes, particularly dendritic cells, mature B cells, and subpopulations of T cells. How CCL20 is systemically scavenged is currently unknown. Here, we identify that fluorescently labeled human and mouse CCL20 are efficiently taken-up by the atypical chemokine receptor ACKR4. CCL20 shares ACKR4 with the homeostatic chemokines CCL19, CCL21, and CCL25, although with a lower affinity. We demonstrate that all 4 human chemokines recruit β-arrestin1 and β-arrestin2 to human ACKR4. Similarly, mouse CCL19, CCL21, and CCL25 equally activate the human receptor. Interestingly, at the same chemokine concentration, mouse CCL20 did not recruit β-arrestins to human ACKR4. Further cross-species analysis suggests that human ACKR4 preferentially takes-up human CCL20, whereas mouse ACKR4 similarly internalizes mouse and human CCL20. Furthermore, we engineered a fluorescently labeled chimeric chemokine consisting of the N-terminus of mouse CCL25 and the body of mouse CCL19, termed CCL25_19, which interacts with and is taken-up by human and mouse ACKR4.